Made to Fit: How Practices Vary As They Diffuse - Ansari, Shahzad M.; Fiss, Peer C.; Zajac, Edward J. (Academy of Management Review, 2010)
We extend research on the diffusion of corporate practices by providing a framework for studying practice variation during diffusion processes. Specifically, we theorize about how population-level mechanisms of diffusion link with organization-level mechanisms of implementation that lead to the adaptation of practices. We also identify technical, cultural, and political elements of fit (or misfit) between diffusing practices and adopters and analyze how the process of attaining fit across these elements can trigger different patterns of adaptation.